2005
DOI: 10.1007/bf03395526
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence Class Establishment with Two-, Three-, and Four-Choice Matching to Sample by Senior Citizens

Abstract: In Experiment 1, 12 senior citizens from the community were trained with 18 sets of conditional discriminations. Training included 2-, 3-, and 4-choice matching-to-sample (MTS) configurations in linear series (LS), many-to-one (MTO), and one-to-many (OTM) training structures. Training structure order was counterbalanced across participants. The design permitted tests for class establishment ranging from 2 classes of 3 stimuli each to 4 classes of 4 stimuli each in the LS , MTO, and OTM structures. ThE3 experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
36
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 25 publications
12
36
0
11
Order By: Relevance
“…Estudos sobre emergência de relações condicionais arbitrárias entre estímulos, sobretudo aqueles baseados no paradigma de equivalência de estímulos (Sidman & Tailby, 1982), tipicamente são realizados utilizando procedimentos de pareamento ao modelo (Arntzen & Holth, 2000a;de Rose, Kato, Thé, & Kledaras, 1997;McIlvane et al, 1987;Moreira, Todorov, & Nalini, 2006;Saunders & Green, 1999;Saunders, Chaney, & Marquis, 2005;Sidman, 1994). Embora esse procedimento tenha se mostrado adequado para o estudo de relações emergentes, as variáveis das quais a formação de classes de equivalência é função ainda não são bem conhecidas (Smeets, Barnes-Holmes, & Cullinan, 2000;Stromer, McIlvane, & Serna, 1993).…”
unclassified
“…Estudos sobre emergência de relações condicionais arbitrárias entre estímulos, sobretudo aqueles baseados no paradigma de equivalência de estímulos (Sidman & Tailby, 1982), tipicamente são realizados utilizando procedimentos de pareamento ao modelo (Arntzen & Holth, 2000a;de Rose, Kato, Thé, & Kledaras, 1997;McIlvane et al, 1987;Moreira, Todorov, & Nalini, 2006;Saunders & Green, 1999;Saunders, Chaney, & Marquis, 2005;Sidman, 1994). Embora esse procedimento tenha se mostrado adequado para o estudo de relações emergentes, as variáveis das quais a formação de classes de equivalência é função ainda não são bem conhecidas (Smeets, Barnes-Holmes, & Cullinan, 2000;Stromer, McIlvane, & Serna, 1993).…”
unclassified
“…Previous studies in adults have shown that DMTS generates high yields of derived responding. For example, Saunders et al (2005) found that senior citizens experiencing DMTS had higher yields of responding in accordance with stimulus equivalence than participants experiencing simultaneous matching. Additionally, some studies have indicated that an experience with longer delays is more effective than an experience with short delays in generating responding in accordance with stimulus equivalence (Arntzen, 2006) or symmetry alone (Vaidya & Smith, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have provided data suggesting that MTO is the most effective training structure (Saunders, Saunders, Williams, & Spradlin, 1993;Saunders et al, 2005;Saunders, Drake, & Spradlin, 1999), while other studies have shown that the OTM training structure is more effective (Arntzen, 2004;Arntzen & Holth, 1997. Some of the studies reporting the superiority of MTO have included children as participants (Arntzen & Vaidya, 2008;Saunders et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A estrutura pode ser linear, na qual se ensinam as relações entre um conjunto de estímulos em relação ao próximo previamente determinado, ou seja: AB -BC -CD etc. ; a estrutura é chamada de "um para muitos", quando há um conjunto de estímulos base que é usado como referência (modelo) para o ensino de todas as relações, como, por exemplo, AB -AC -AD; e a estrutura pode ser chamada de "muitos para um", quando os diferentes conjuntos de estímulos -B, C, D -são relacionados como modelo a um mesmo conjunto de estímulo -A, que serve sempre como base para a apresentação dos estímulos de comparação: BA, CA, DA (Saunders, Chaney & Marquis, 2005). De Rose, Kato, Thé e Kledaras (1997) afirmam, com base na análise dados de pesquisas de outros autores, que, para pessoas com deficiência intelectual, o arranjo "muitos-para-um" mostra-se mais eficaz.…”
Section: Equivalência De Estímulosunclassified